MLVA and LPS Characteristics of Brucella canis Isolated from Humans and Dogs in Zhejiang, China - Piao, Dongri; Wang, Heng; Di, Dongdong; Tian, Guozhong; Luo, Jiantong; Gao, Wenjie; Zhao, Hongyan; Xu, Weimin; Fan, Weixing; Jiang, Hai (Frontiers in Veterinary Science, 2017)
Background Brucella canis is a pathogenic bacterium that causes brucellosis in dogs, and its zoonotic potential has been increasing in recent years. B. canis is a rare source of human brucellosis in China, where Brucella melitensis has been the major pathogen associated with human brucellosis outbreaks. In late 2011, a case of a B. canis infection was detected in a human patient in Zhejiang Province, China. To compare the genotypes between strains of B. canis isolated from the patient and from dogs, a multiple-locus variable-number tandem-repeat analysis (MLVA-16) was performed. In addition, the lipopolysaccharide-synthesis-related genes were analyzed with the B. canis reference strain RM6/66. Results 32 B. canis strains were divided into 26 genotypes using MLVA-16 [Hunter-Gaston Diversity Index (HGDI) = 0.976]. The HGDI indexes for various loci ranged between 0.000 and 0.865. All four Hangzhou isolates were indistinguishable using panel 1 (genotype 3) and panel 2A (genotype 28). However, these strains were distinctly different from other isolates from Beijing, Jiangsu, Liaoning, and Inner Mongolia at Bruce 09. The emergence of a human B. canis infection was limited to an area. Comparative analysis indicated B. canis from canines and humans have no differences in lipopolysaccharide-synthesis locus. Conclusion The comprehensive approaches have been used to analyze human and canine B. canis isolates, including molecular epidemiological and LPS genetic characteristics. Further detailed analysis of the whole genomic sequencing will contribute to understanding of the pathogenicity of B. canis in humans.